Våld och hot på arbetsplats : En kvalitativ och kvantitativ studie på Piteå kommunanställda personliga assistenters arbetssituation - Forsell, Linda; J Lifvakt, Jeanette (2016)
The purpose of this thesis was to investigate the existence of violence and threats of violence in the workplace of municipal employed personal assistants. Research questions were: does violence or threats of violence occur at the workplace? What type of violence and threats are the employees subject to? What are the psychosocial health effects of violent and threatening situations? Which preventive measures are provided by the managers? Both a qualitative and quantitative approach have been used as data collection methods. The qualitative part consist of Interviews were conducted with six managers and a survey was administered to 113 personal assistants. The frame of reference includes Karasek and Theorell´s theory of work stress associated with insufficient job control and social support, previous research by various authors and regulations from Arbetsmiljöverket. The results were thematically analyzed, the survey by descriptive statistics and the interviews under relevant headings. The result reveals that violence and threats do occur on personal assistants workplaces, but to varying extent. The kind of violence the personnel is most exposed to are physical, such as kicks and punches. Those who are exposed feel, in comparison to unexposed a lack of support from the manager.Keywords: Personal assistant, Piteå Kommun, First line manager, violence and threats, health-unhealth, work environment management, support, Karasek’s demand-control model, knowledge Validerat; 20160623 (global_studentproject_submitter)